The immigrant [videorecording (DVD)] - Gray, James, 1969-; Cotillard, Marion, 1975-; Phoenix, Joaquin; Renner, Jeremy; Sarafyan, Angela, 1983- (Anchor Bay Entertainment, 2015)
Ewa Cybulski and her sister sail to New York from their native Poland in search of a new start and the American dream. When they reach Ellis Island, doctors discover that Magda is ill, and the two women are separated. Ewa is released onto the mean streets of Manhattan while her sister is quarantined. Alone, with nowhere to turn and desperate to reunite with Magda, Ewa quickly falls prey to Bruno, a charming but wicked man who takes her in and forces her into prostitution.